Dual Economies and International Total Factor Productivity Differences - Areendam Chanda; Carl-Johan Dalgaard (University of Copenhagen, Economic Policy Research Unit (EPRU), 2003)
This paper argues that a significant part of measured TFP differences across countries is attributable not to technological factors that affect the entire economy neutrally, but rather, to variations in the structural composition of economies. In particular, the allocation of scarce inputs between agriculture and non-agriculture seems to be important. We provide a theory which links the institutional framework to the long-run composition of the economy, and thereby to measured TFP and income per worker. A decomposition analysis suggests that between 30 and 50 percent of the international variation in TFP can be attributed to the composition of output. Estimation exercises suggest that recent findings of a conducive effect from institutions, and to some extent, geography, on long-run prosperity and TFP, may be thus explained.
Keywords: O41; O47; O50; 330; dual economy; structural change; total factor productivity; institutions; geography; Dualökonomie; Produktivität; Wirtschaftsgeographie